Development of RPG-Based Mathematics Educational Games with the Waterfall Method on Fraction Material for Elementary School Students - Satriyo, Azis; Azis, Abdul; Saputri, Fiqih Hana; Ferawati, Ferawati (Politeknik Ganesha Medan, 2025)
Mathematics is one of the subjects that plays an important role in everyday life and in developing logical thinking and problem-solving skills. One of the topics that often poses a challenge for elementary school students is fraction numbers. Fractions are often considered an abstract and difficult concept to understand because they involve numerical representations that differ from whole numbers. This difficulty frequently leads to a lack of interest in learning mathematics, ultimately affecting students' academic performance. The data collection stages applied include interviews, observations, and the distribution of questionnaires. The development of this learning media follows the Waterfall model, which aims to design improvements to the existing system. The results of the User Acceptance Test reveal that this game received a user perception score of 90.5%, categorizing it as